Development of procedure and analysis of hard rock drilling - Omdal, Kjetil (University of Stavanger, Norway, 2015)
Master's thesis in Petroleum engineering Over the last few years the petroleum industry have experienced a drastically increase in drilling costs. At the same time the oil prize has been highly unstable resulting in an increased focus on reducing drilling costs. The aim of this thesis is to look for cost reducing measures when drilling in hard rock formations offshore. Drilling in hard formations is both challenging and time consuming as a consequence of Low Rate of Penetration (ROP) and high None Productive Time (NPT). Typically hard rock stones encountered offshore are limestone, basalt, chart and chalk which for instance can be found in the NCS, on Iceland and offshore Faroe Islands. This thesis presents: • The status of the current drilling technologies and its potential while identifying the current problems experienced when drilling in hard rocks. • Mitigation for hard rock drilling problems • Development of a procedure that can be used for planning wells offshore with aim to reduce cost • Case study of the procedure with a well from the NCS The developed procedure is based on analysis of old well and when planning new well. By doing this, one can implement percussive drilling along with rotary to increase ROP and reduce NPT, and reduce the overall drilling operational cost. The result from the case study indicates a cost reduction of 18,8% when implementing percussive drilling. Due to several assumptions more detailed research is required before percussive drilling can be concluded as a solution.